Relation of meniscus pathology to prevalence and worsening of patellofemoral joint osteoarthritis: the Multicenter Osteoarthritis Study. Issue 7 (July 2018) - Hart, H.F.; Crossley, K.M.; Felson, D.; Jarraya, M.; Guermazi, A.; Roemer, F.; Lewis, C.E.; Torner, J.; Nevitt, M.; Stefanik, J.J.
Summary: Objective: To determine the relationship of meniscal damage to magnetic resonance imaging (MRI) features of compartment-specific patellofemoral joint (PFJ) osteoarthritis (OA) at baseline and 2 years later. Method: Individuals from a prospective cohort of individuals aged 50–79 with or at risk of knee OA were included. At the 60-month and 84-month study visit, Whole-Organ MRI Score (WORMS) was used to assess meniscal tears and extrusions as well as cartilage damage and bone marrow lesions (BMLs) in the medial and lateral patella and trochlea. Worsening of structural features was defined as any increase in WORMS score from 60 to 84 months. Logistic regression was used to determine the cross-sectional and longitudinal relation of meniscus damage to features of compartment-specific PFJ OA. Results: Relative to knees without lateral meniscal pathology at baseline, those with grades 3–4 lateral meniscal tear and extrusion had greater risk of worsening of cartilage damage in the lateral PFJ 2 years later (Risk ratio: 1.7 [95% CI: 1.1–2.7) and (1.7 [1.2–2.5]), respectively. Relative to those without medial meniscal pathology at baseline, those with grades 1–2 (0.6 [0.4–0.9]) and 3–4 (0.7 [0.5–1.0]) medial meniscal tears had lower risk of worsening of BMLs in the medial PFJ 2 years later. Conclusion: Meniscal tear and extrusion are associated with increased risk of medial and lateral PFJ OA and more severe meniscal pathology is associated with worsening of PFJ OA 2 years later. Lateral meniscal pathology appears to be more detrimental to the lateral PFJ.